Traverser les banlieues littéraires : entre sensationnalisme et banalité quotidienne - Serena Cello (Itinéraires)
Within the conflicted relationship between centre and suburbs known as “contemporary social problem,” we find the “banlieue literature” born after French urban disorders in 2005. Throughout six novels published one year later, we question the contemporary literary representation of these places in a problematic correlation between sensationalism and banality. Those texts want to replace margins at the centre of the actual debate as well as the French literature, contributing also to engender other perspective’s analysis to the most prevalent ones.